Experimental Study of Cranial Injuries Due to Blunt Force Trauma: Sus scrofa domestica Model - Otero, Felipe (2019)
Cranial blunt force trauma is of major concern in forensic sciences. The aim of this study is to shed light on cranial bone trauma caused by blunt weapons from an experimental perspective. The experimentation involved the production of blunt injuries to 21 pig skulls with different objects: metal hammer, wooden club (baseball bat), stone and boleadora. These blunt objects were chosen because they can be easily used as homicidal weapons since they are common elements that can be seen in daily situations today. The marks produced were recorded and analyzed using quantitative and qualitative variables. The results showed that it is possible to identify the blunt weapon that caused the injury through the analysis of variables such as maximum diameter or depth of the bone injury. Furthermore, it was observed that depending on the damage, the injury could be associated with a blunt object with specific characteristics.